2016 IEEE International Conference on Management of Innovation and Technology (ICMIT) 2016
DOI: 10.1109/icmit.2016.7605001
|View full text |Cite
|
Sign up to set email alerts
|

E-business capabilities in developed and developing countries: Different or the same?

Abstract: 2016 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.Abstract -This paper compares the e-business capabilities in developed and developing countries; in particular the awareness and usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Waigwa and Njeru (2016), in their study on the factors influencing management of procurement contracts in public security agencies, concluded that public sector entities utilize eprocurement to obtain gains such enhanced efficiency and cost savings, shorter procurement cycles and enhanced accountability to reduce corruption in procurement by avoiding face to face dealing with service providers. Adebanjo, Tickle, Lin and Bourlakis (2016), on e-business capabilities in developed and developing countries, posited that the public sector had widely accepted e-procurement and its utilization graph has grown exponentially. According to Chimberengwa et al (2015), in the research on procurement processes at Gwanda Provincial Hospital, Matabeleland South Province Zimbabwe stated that Zimbabwean public sector is still to fully embrace e-procurement.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Waigwa and Njeru (2016), in their study on the factors influencing management of procurement contracts in public security agencies, concluded that public sector entities utilize eprocurement to obtain gains such enhanced efficiency and cost savings, shorter procurement cycles and enhanced accountability to reduce corruption in procurement by avoiding face to face dealing with service providers. Adebanjo, Tickle, Lin and Bourlakis (2016), on e-business capabilities in developed and developing countries, posited that the public sector had widely accepted e-procurement and its utilization graph has grown exponentially. According to Chimberengwa et al (2015), in the research on procurement processes at Gwanda Provincial Hospital, Matabeleland South Province Zimbabwe stated that Zimbabwean public sector is still to fully embrace e-procurement.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…1.4 Research Objectives E-business has the potential to transform businesses and increase revenue as seen with several large organisations, multinationals, and as indicated in numerous studies in developed countries (Zhu, Kraemer and Xu, 2006;Chen and Holsapple, 2013). The dynamics of use, culture and challenges often differ from country to country (Adebanjo et al, 2016) and as a result, this research sets out to achieve the following objectives:…”
Section: Purpose Of the Researchmentioning
confidence: 99%
“…In this era of globalising economies, many SMEs are making use of e-business to serve customers in geographically dispersed locations and are becoming more internationally focused (Savrul, Incekara and Sener, 2014). Research has shown that SMEs are not being left behind in the adoption of e-business and in fact, ebusiness in SMEs has moved from a 'nice to have', to a requirement in order to transact business with some large companies and government establishments (Afolayan et al, 2015;Adebanjo et al, 2016). As indicated by Seyal and Rahman (2013) in their study on Bruneian SMEs, businesses adopt e-business in order to increase sales, improve decision making, improve customer service, provide better access to information and compete effectively.…”
Section: E-business Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes the companies to incur losses of goods and items annually affecting their economy (Hillman, 2012). Most companies in developing countries still use manual ways of keeping information for warehouse storage and transaction which is a very inefficient method for large companies and organizations handling large warehouses (Adebanjo et al, 2016). The traditional ways of managing warehouse leads to low productivity (Nikoloski, 2014).…”
mentioning
confidence: 99%